A narração de futebol no contexto de rádio expandido - Götz, Ciro Augusto Francisconi (2022)
From the 1930s to the present, radio and soccer continue to be consumed by audiences that have been renewed for generations. If, on the one hand, several idols arose -responsible for memorable achievements- whether from the Brazilian Team or the beloved teams, loved by millions of listeners around the country, on the other hand one of the most important functions of sports radio journalism of all time was consacrated -soccer narration. The radio has gone through numerous stages of adaptation, whether in relation to the economy, politics, market and technology. The following research investigates narration in the context of expanded radio (KISCHINHEVSKY, 2016), in the midst of convergence (JENKINS, 2008), multiplicity of supply (BRITTOS, 2002), between radiomorphosis processes (PRATA, 2008), of a medium that is present on cell phones, computers, applications and digital platforms such as YouTube, mixing elements of radiophonic language and sound resources. The general objective was to identify the characteristics and the role played by the narrators from Porto Alegre, Haroldo de Souza (Rádio Grenal) and César Weiler (Rádio Pachola), from Rio de Janeiro, José Carlos Araújo (Super Rádio Tupi) and Rafa Penido (Coluna do Fla), from São Paulo, José Silvério (Rádio Bandeirantes) and Doni Vieira (Web Rádio Craque Neto) and, from Belo Horizonte, Alberto Rodrigues (Rádio Itatiaia) and Beto Guerra (Web Rádio Galo) in the current scenario. Work environments, market dynamics, strategies and expressive resources (PRIETO CASTILLO, 1984) of persuasion and the predominant techniques and styles (SOARES, 1994; SCHINNER, 2004) were observed. The methodology of the multiple case study (YIN, 2015) was applied, and the main evidence obtained through fragments of interviews from the YouTube channel Projeto As Vozes do Gol (GÖTZ, 2021), also taking into account excerpts from games, bids and goals transmitted by the narrators through their respective broadcasters. It was found that the soccer narrator in an expanded radio context is a hybrid announcer, adapted to platforms, multitasking, influencer, mediator, protagonist and capable of describing the moves of a given match with emotion and improvisation for different audiences. And, in this scenario, the web narrator appears as a type of intermediary speaker between radio and television narrators, molded between parasonorous resources, locution and slower rhythms, whose main features are interactivity, engagement, improvisation and emotional attributes.